How can a manufacturing company stay competitive in a changing market? - Rexed, Filippa; Wikman, Matilda (My University, 2020)
Emerson is a manufacturer of measurement instruments and is the leading manufacturer in several large industries. Now, Emerson wants to grow in new customer segments, where the Chemical segment has been identified as attractive. To grow in this segment, Emerson must understand customer needs to differentiate their offering to fit a new type of customer. The aim of the study is thereby to identify customer needs where Emerson can differentiate their offering to Chemical customers and to understand what Emerson can do to take advantage of the market opportunity of growth with radar technology in the Chemical segment. A case study of Emerson has been performed. Data was collected through four research methods, a literature review, interviews, observations and secondary data. The interviews were performed in two phases, the first one with employees at Emerson, aimed at creating an understanding of Emerson and the current situation. The second one was performed with companies operating in the Chemical segments, to create an understanding of their needs. The data collection showed patterns in common problems and challenges present at the Chemical companies. The basic need of the customers was common amongst them, to maximise uptime and reduce stops in the production. Furthermore, the Chemical customers lacked knowledge regarding how to solve issues in complex applications. Moreover, it was perceived that all radar level measurement instruments had more or less equal performance in standard applications. Thereby, the analysis propose that Emerson should continue to be a differentiator and use the Chemical customers’ needs to introduce new unique offerings to the market. Several suggestions are presented in the study, such as self-diagnostic services and an extended customer support. Furthermore, the Chemical customer’s needs have implications on Emerson’s business model and the organisational structure, where changes are proposed for Emerson to be successful with the Chemical customers. Moreover, three suggestions are presented to target the customer needs; radical innovation, involving customers and cross-functionally integrating departments.
Keywords: Emerson; Rosemount; customer needs; product offering; differentiation; innovation